2019
DOI: 10.1111/1365-2435.13334
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection favours a larger eye in response to increased competition in natural populations of a vertebrate

Abstract: Eye size varies notably across taxa. Much work suggests that this variation is driven by contrasting ecological selective pressures. However, evaluations of the relationship between ecological factors and shifts in eye size have largely occurred at the macroevolutionary scale. Experimental tests in nature are conspicuously absent. Trinidadian killifish, Rivulus hartii, are found across fish communities that differ in predation intensity. We recently showed that increased predation is associated with the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
(132 reference statements)
1
15
0
Order By: Relevance
“…The connection between brain structures and eye size is also potentially adaptive. Previous work in killifish has shown that increases in eye size are associated with greater survival and enhanced growth in sites that lack predators (Beston & Walsh, 2019). This suggests that the increased competition for food in RO sites selects for increased eye size and that brain structures may evolve as an indirect byproduct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The connection between brain structures and eye size is also potentially adaptive. Previous work in killifish has shown that increases in eye size are associated with greater survival and enhanced growth in sites that lack predators (Beston & Walsh, 2019). This suggests that the increased competition for food in RO sites selects for increased eye size and that brain structures may evolve as an indirect byproduct.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary shifts in eye size have also been linked to changes in ecological conditions. For example, studies have quantified selection on eye size due to such factors as light availability (Hall, 2008; Hiller‐Adams & Case, 1988; Kröger & Fernald, 1994; Veilleux & Lewis, 2011), predation (Glazier & Deptola, 2011; Møller & Erritzøe, 2010; Nilsson et al., 2012), and competition (Beston et al., 2017, 2019; Beston & Walsh, 2019). This growing body of work illustrating similar shifts in brain and eye size in response to ecologically mediated selection foreshadows the possibility that selection favors coordinated shifts in these neurosensory systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have linked selection for large eye/pupil size to e.g. dim light habitats and nocturnal behaviour (Martinez‐Ortega, Santos, & Gil, 2014; Schmitz & Wainwright, 2011; Warrant, 2004) or to competition (Beston & Walsh, 2019) and predation risk per se (Freund & Olmstead, 2000; Glazier & Deptola, 2011; Møller & Erritzoe, 2010; Nilsson et al., 2012). Such changes may be of particular importance in the many teleost fish that lack a pupillary sphincter muscle and, hence, have a pupil that is fixed in size and not responsive to ambient light intensity (Douglas, 2018; Helfman et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in nocturnality may thus select for facultative and rapid adaptations of the visual system, enabling night‐time activity. Such changes in diel rhythms have recently been suggested as the selective agent driving evolutionary shifts in eye size among populations of the Trinidadian killifish Rivulus hartii (Beston & Walsh, 2019). Furthermore, a recent study demonstrated that selection pressures on activity patterns have been the main drivers for evolutionary divergence in the mammalian eye (Baker & Venditti, 2019).…”
Section: Introductionmentioning
confidence: 99%